2018
DOI: 10.7150/thno.22467
|View full text |Cite
|
Sign up to set email alerts
|

Identification of type IV collagen exposure as a molecular imaging target for early detection of thoracic aortic dissection

Abstract: Thoracic aortic dissection (TAD) is an aggressive and life-threatening vascular disease and there is no effective means of early diagnosis of dissection. Type IV collagen (Col-IV) is a major component of the sub-endothelial basement membrane, which is initially exposed followed by endothelial injury as early-stage event of TAD. So, we want to build a noninvasive diagnostic method to detect early dissection by identifying the exposed Col-IV via MRI.Methods: Col-IV-targeted magnetic resonance/ fluorescence dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…CB, a nontoxic receptor binding subunit, can specifically bind the monosialoganglioside GM1 in the hippocampus, leading to increased concentrations of nanosystems in the brain . Gadolinium was incorporated into the system for facilitating MRI . Compared with iron oxide NP‐based MRI agents, Gd‐based MRI agents could be generally used for different organs and are easily metabolized, which benefits monitoring the condition of AD .…”
Section: Introductionmentioning
confidence: 99%
“…CB, a nontoxic receptor binding subunit, can specifically bind the monosialoganglioside GM1 in the hippocampus, leading to increased concentrations of nanosystems in the brain . Gadolinium was incorporated into the system for facilitating MRI . Compared with iron oxide NP‐based MRI agents, Gd‐based MRI agents could be generally used for different organs and are easily metabolized, which benefits monitoring the condition of AD .…”
Section: Introductionmentioning
confidence: 99%
“…The anti-actin antibody (1:1000; Proteintech Group, USA) served as control. The protein bands were visualized with enhanced chemiluminescence reagents (ECL), and the signal densitometry was quanti ed by an observer blinded to the groups of the animals using western blotting detection system (Quantity One, Bio-Rad Laboratories, USA) [28] .…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Endothelial injury is an important pathophysiological step toward atherosclerotic stenosis,[ 80 ] an overhealing reaction of the blood vessels to the injury. [ 81 82 ] Studies have shown that various factors can lead to damage of the endothelium,[ 83 ] including inflammatory reactions, physical stimulation, chemical poisons, concurrency of related diseases, aging, and a deficiency of Vitamin D.[ 84 85 86 87 88 ] However, the exact mechanism of endothelial injury is not yet fully understood.…”
Section: Onclusionmentioning
confidence: 99%